Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/1365-2745.12882
|View full text |Cite
|
Sign up to set email alerts
|

Declining growth of deciduous shrubs in the warming climate of continental western Greenland

Abstract: 1. Observational and experimental studies have generally shown that warming is associated with greater growth and abundance of deciduous shrubs in arctic ecosystems. It is uncertain, however, if this trend will persist in the future.2. Our study examined growth responses of deciduous shrubs to climate change over the late 20th and early 21st centuries near Kangerlussuaq in western Greenland. We combined shrub dendrochronology, stable isotope analysis and weekly measurements of leaf gas exchange to examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
84
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(102 citation statements)
references
References 54 publications
12
84
2
Order By: Relevance
“…Within glacial landscapes, variability in local soil conditions has further consequences for vegetation response to climate. For example, while shrub growth often responds positively to growing season temperature, temperature-induced moisture limitation may constrain growth during particularly hot years at drier locations such as uplands (Ackerman et al 2017, Gamm et al 2017. Such local variability in soil conditions interacts with regional glacial geology and broad-scale climate patterns to create a hierarchical structure of controls on tundra vegetation growth (Myers-Smith et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within glacial landscapes, variability in local soil conditions has further consequences for vegetation response to climate. For example, while shrub growth often responds positively to growing season temperature, temperature-induced moisture limitation may constrain growth during particularly hot years at drier locations such as uplands (Ackerman et al 2017, Gamm et al 2017. Such local variability in soil conditions interacts with regional glacial geology and broad-scale climate patterns to create a hierarchical structure of controls on tundra vegetation growth (Myers-Smith et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Dendroecology, the study of annual growth increments in woody plants, has become a popular method within the last two decades for analyzing climate response of arctic vegetation (See studies included in Myers-Smith et al 2015a, Young et al 2016, Ackerman et al 2017, Gamm et al 2017. This method is particularly well-suited for arctic tundra, since many plant species are long-lived and interannual climate is highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…More surprisingly, recent dendrochronology studies from Greenland and Svalbard report on a deviation from the aforementioned clear and positive summer temperature responses (Forchhammer, ; Gamm et al, ; Opała‐Owczarek et al, ). In a coastal site in Svalbard, with twice as high precipitation levels as our inland site, Opała‐Owczarek et al () proposed that soil moisture and soil structure have a larger influence on S. polaris ring growth than temperature .…”
Section: Discussionmentioning
confidence: 96%
“…polaris growth in our study, with the possible exception that the extremely rainy summer in 2013 resulted in a prominent reduction in heath habitat's above‐ground biomass. Furthermore, in spite of increasing summer temperatures, Gamm et al () observed a temporal decline in ring growth in continental Western Greenland for Betula nana and Salix glauca . They suggested this could be due to increased defoliation from herbivory and increasing moisture limitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation